Virtual learning environments: Contributions to Education - Elizabeth Luque Alcívar, Karina; María San Andrés Laz, Esthela; Fernando Pazmiño Campuzano, Marcos (International Journal of Psychosocial Rehabilitation, 2020)
Information and Communication Technologies currently provide the knowledge society with a variety of computer tools that allow them to improve their work environments. One of these applications is e-learning platforms, which within the educational sector are becoming a complementary resource to improve educators' teaching methods. The objective of this article is to determine the degree of importance that teachers in the central part of the city of Chone give to Virtual Learning Environments as a support tool in the teaching-learning process. The present investigation started from an exhaustive bibliographic review and was complemented with the use of the descriptive method with a qualitative and quantitative approach. Likewise, a survey was applied as a data collection instrument that was designed on the Google Forms website. In addition, the inductive-deductive method was used to know the different management systems of learning most manipulated worldwide and in turn describe the advantages of using you in education. The results revealed that 50% of the surveyed teachers are using different technological learning strategies to turn their classes into interactive environments and continue with education from anywhere, thus improving educational quality.